PEMIKIRAN PENDIDIKAN ISLAM DALAM ERA DIGITAL: TANTANGAN DAN PELUANG UNTUK GENERASI MUDA - Aisa Agustin (PT. Habe Cendekia Utama, 2025)
The digital era has had a significant impact on various aspects of life, including Islamic education. The purpose of this study is to examine various problems that arise as a result of such rapid changes, facing all these challenges so that the next generation has the resilience to adapt to various changes in the era. This study uses a qualitative approach with library research and phenomenology methods. The results of the study indicate that the problems that arise as challenges to Islamic education are: moral decadence, the emergence of non-educational media that are easily consumed by children, inappropriate use of social media, situations that demand competition in various aspects, the necessity of democracy and modern developments, demands to survive crises and maintain what has been achieved, demands to compete on a regional, national and international scale, demands to adapt to rapid changes.